On the Failed Italian Intervention in Transcaucasia in 1919 - V. M. Mukhanov (Международная аналитика, 2016)
In 1919, the idea appeared to replace the British occupation forces in the Caucasus with the Italian ones. The article discusses the process of making a decision on the issue, the position of various British political and military leaders, as well as the impact of the political situation in Italy on the final decision concerning the transfer of the Italian troops to Caucasus. It was a dramatic change in the political life in Italy that has led to the cancellation of military campaign in the Caucasus and formation of the Italian occupation forces.